Mathematical Modeling of Pollutants Dispersion in the Atmosphere - Kafle, Jeevan; Adhikari, Krishna Prasad; Poudel, Eeshwar Prasad; Pant, Ramesh Raj (Journal of Nepal Mathematical Society, 2024)
Air pollution is one of the biggest problems in both developed and developing countries. Mathematical modeling is widely applied to assess how air pollutants impact on human and ecological health. In this paper, the fundamental behavior of the plumes along with stack height and the underlying assumptions of the Gaussian plume model were assessed. Additionally, the equation for advection and diffusion was also developed to analyze the pollutants concentration of brick kilns. Basically, the model considers the height, emission sources, eddy diffusivity, and wind profile as parameters by adopting the fundamental approaches of the model. Interestingly, the results revealed that when the stack height is reduced, pollutants are more prominent whereas when the stack height is increased, the pollutants are less prevalent along the x-axis. There is a close relationship between wind velocity and pollutants dispersion. The model illustrates that stronger winds tend to increase the dispersion of air pollutants; hence, areas with stronger winds typically have lower air pollution concentrations. The insights of this work will directly contribute to environmental sustainability by mitigating pollutants concentration, especially in the core urban areas. Additionally, the work is also applicable for the researcher and academia to select the optimal measurement techniques and ways forward for controlling the pollution level in the atmosphere.